Research progress on metabolism-related biomarkers of frailty in the elderly - PAN Yi-ming, LI Yun, MA Li-na (Jichu yixue yu linchuang, 2021)
Frailty is a common syndrome in the elderly, identified by the decline of physiological functions in multiple organ systems, which may lead to adverse outcomes such as falls, cognitive impairment, hospitalization or death. Early diagnosis of frailty is of great value in promoting healthy aging. At present, it can only be diagnosed by assessment tools in clinical without specific biomarkers. Frailty is often accompanied by metabolic disorders in many aspects, such as changes in metabolism of energy, muscle, bone, and in endocrine system. The study of metabolism-related biomarkers can help early diagnosis and intervention of frailty.